2018
DOI: 10.1016/j.onehlt.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Participatory epidemiology of endemic diseases in West African cattle – Ethnoveterinary and bioveterinary knowledge in Fulani disease control

Abstract: Fulani pastoralists in Nigeria lack adequate access to good quality veterinary services and often resort to treating their animals themselves. There are several negative aspects to this, including poor treatment outcomes, misuse of veterinary drugs and subsequent resistance, and further barriers to good relations between pastoralists and veterinary services. A participatory epidemiology survey was undertaken in Fulani communities, to examine their ability to diagnose and treat bovine diseases. Qualitative part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…The P -values are displayed at the top, and Pearson correlation coefficients are displayed at the bottom ( Figure 11 ). Various ethno-veterinary ethnoveterinary studies, such as Majekodunmi et al ( 61 ) from West Africa, Catley ( 62 ) from East Africa, Raza et al ( 63 ) from Pakistan's Cholistan desert, Rezende et al ( 64 ) from Minas Gerais, and Haq et al ( 65 , 66 ) from the Himalayas, have shown similar hierarchical clustering, multidimensional scaling, and associations.…”
Section: Resultsmentioning
confidence: 92%
“…The P -values are displayed at the top, and Pearson correlation coefficients are displayed at the bottom ( Figure 11 ). Various ethno-veterinary ethnoveterinary studies, such as Majekodunmi et al ( 61 ) from West Africa, Catley ( 62 ) from East Africa, Raza et al ( 63 ) from Pakistan's Cholistan desert, Rezende et al ( 64 ) from Minas Gerais, and Haq et al ( 65 , 66 ) from the Himalayas, have shown similar hierarchical clustering, multidimensional scaling, and associations.…”
Section: Resultsmentioning
confidence: 92%
“…As a result, health communication campaigns (advocating cooking and better hygiene, for example) had limited impacts on culturallyembedded risk behaviors-highlighting that all interventions need to be adapted to cultural settings (6). These citations are examples of rigorous and impactful contributions from qualitative researchers to the control and prevention of zoonoses (64)(65)(66)(67), or the effectiveness of responding organizations (68,69).…”
Section: Interviewsmentioning
confidence: 99%
“…Control and surveillance has been progressively scaled back in many developing countries in favour of emerging, transboundary and zoonotic diseases (Majekodunmi et al, 2018). Even though, any challenge facing pastoral livestock will directly affect the community, endemic disease management is left to livestock owners and private sector service providers (Lemma and Alemu, 2020)..…”
Section: Introductionmentioning
confidence: 99%